University undergraduates’ career choice commitment: An analysis of two samples - Urbanavičiūtė, Ieva (Psichologija, 2009)
Career development is a rather popular research area. Previous studies have revealed numerous factors that are relevant for the process of career planning during various stages of life. The constantly changing and challenging world, as well as the demand of new competencies in the labour market, draw attention to the time when an individual leaves school and sets future career goals preparing to enter the world of work. There is still an open question which psychological factors could be crucial for the smooth career goal setting at this time. The present study aims to explore one’s future career intentions after one has already chosen a study major. The study had the following goals: to analyse whether career choice commitment (having future career goals related to one’s major) can be predicted by the level of career choice satisfaction, expected real-ideal and real-prestigious job fit, and personality factors such as neuroticism and conscientiousness, conducting analysis in two samples; to explore the differences of the predictors of career goal commitment between Sample 1 and Sample 2. 185 Vilnius University undergraduates (131 females, 54 males) took part in the study. The primary sample was then subdivided into two parts, excluding the middle range data: Sample 1 consisted of participants whose career choice satisfaction was low (n = 55), and Sample 2 consisted of participants whose career choice satisfaction was high (n = 76). A two-step hierarchical regression model analysis was run in both samples. The results revealed multiple significant predictors of career choice commitment in Sample 1: the level of career choice satisfaction (low level in this sample), expected real-prestigious job fit, and, to a lesser extent, expected real-ideal job fit were significant predictors in the primary regression model. Adding neuroticism and conscientiousness to the regression model significantly changed it by increasing its R2, although only neuroticism was a significant predictor. On the contrary, in Sample 2, the level of career choice satisfaction (high in this sample) was the dominant predictor of career choice commitment, followed only by expected real-prestigious jog fit. Adding personality variables to the model didn’t produce a significant change in this case. The results provide the basis for further theoretical and practical implications in career counselling and set guidelines for the future research.